Implementation and obstacles to the multi-sectoral approach in COVID-19 tracing and testing at Puskesmas: experience from Cilacap, Central Java - Maulana, Yusup (BKM Public Health and Community Medicine, 2021)
Objective: This study describes the Covid-19 tracing and testing activities at the Karangpucung II Health Center, Cilacap, Central Java, and the obstacles and multi-sectoral cooperation in handling them. Contents: The data comes from the daily Covid-19 reports in the work area and describes how to carry out tracing and testing for Covid-19 and handling of Covid-19, the flow of multi-sectoral cooperation, and obstacles regarding the implementation of policies related to tracking and testing. This health center has an area bordering the Banyumas and Brebes regencies, which has the potential to spread cases, especially with high population mobility. The results of tracing and testing found 439 positive points out of 960 PCR swabs. Swabs with antigen got 25 positive out of 250 examined. Further studies need to focus on the coverage of tracing and testing according to WHO standards, examining one person per 1,000 population every week to measure the rate of transmission in the region.